NADA SAPE’ DAN TEKANAN DARAH: HARMONI MUSIK TRADISIONAL DAYAK BAKATI DALAM MENGONTROL HIPERTENSI PADA LANSIA - Supriono; Astuti Purnamawati, Ditha; Usman; Pratama, Kharisma (Jurnal Riset Keperawatan dan Kesehatan, 2024)
Background: Traditional Sape’ music, a distinctive instrument of the Dayak community, is known for its relaxing effects and potential to reduce blood pressure. Elderly individuals with hypertension often experience elevated blood pressure due to stress and anxiety. Non-pharmacological interventions such as music therapy can serve as an alternative approach to naturally stabilize blood pressure. Objective: To determine the effect of traditional Sape’ music on the blood pressure of hypertensive elderly Dayak Bakati individuals in the working area of Seluas Health Center. Methods: This study employed a pre-experimental design with a one group pretest-posttest approach. Samples were selected using purposive sampling among hypertensive Dayak Bakati elders. The intervention involved listening to traditional Sape’ music for a specific duration. Blood pressure was measured before and after the intervention using a digital sphygmomanometer. Data were analyzed using the Paired Sample t-test with a significance level of p < 0.05. Results: There was a significant reduction in both systolic and diastolic blood pressure after exposure to Sape’ music (p < 0.05). Conclusion: Traditional Sape’ music effectively reduces blood pressure in hypertensive elderly Dayak Bakati individuals. This culturally rooted music therapy can serve as a complementary non-pharmacological approach in hypertension management.